+0  
 
0
548
3
avatar

Let p(x) = 2x^3 - 113 and let q be the inverse of p. Find q(137)

Please be sure to clearly explain your steps and support your arguments. 

I need a really good explanation please! Thank you!

Guest Nov 11, 2014

Best Answer 

 #1
avatar+81061 
+10

Let p(x) = 2x^3 - 113 and let q be the inverse of p. Find q(137)

Let's find the inverse.....let  p(x) = y

y = 2x3 - 113       add 113 to both sides

y + 113  = 2x3     divide both sides by 2

( y + 113 ) / 2   = x3    take the cube root of both sides

3√[( y + 113) / 2]  = x       exchange x and y

3√[( x + 113) / 2]  = y       for "y"  write q(x)

q(x) = 3√[( x + 113) / 2]     so q(137) = 3√[( 137 + 113) / 2] = 3√125  = 5

 

CPhill  Nov 11, 2014
Sort: 

3+0 Answers

 #1
avatar+81061 
+10
Best Answer

Let p(x) = 2x^3 - 113 and let q be the inverse of p. Find q(137)

Let's find the inverse.....let  p(x) = y

y = 2x3 - 113       add 113 to both sides

y + 113  = 2x3     divide both sides by 2

( y + 113 ) / 2   = x3    take the cube root of both sides

3√[( y + 113) / 2]  = x       exchange x and y

3√[( x + 113) / 2]  = y       for "y"  write q(x)

q(x) = 3√[( x + 113) / 2]     so q(137) = 3√[( 137 + 113) / 2] = 3√125  = 5

 

CPhill  Nov 11, 2014
 #2
avatar+91477 
0

That looks like fun Chris :)

Melody  Nov 12, 2014
 #3
avatar
0

Wait, but doesn't ((137+133)/2)^(1/3) simplify into (270/2)^(1/3) which is (135/2)^(1/3), not (125/2)^1/3. 

Guest Aug 2, 2016

10 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details